The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/ente.201900871
|View full text |Cite
|
Sign up to set email alerts
|

Negative Emission Energy Production Technologies: A Techno‐Economic and Life Cycle Analyses Review

Abstract: Negative emission technologies (NETs) are of growing importance for society to meet the atmospheric carbon levels required to maintain global temperatures under sustainable limits. A wide range of NETs have been proposed, but there are limited NET assessments that integrate life cycle analysis (LCA) and techno‐economic analysis (TEA). This Review gathers NET TEA/LCA findings and compares their costs and greenhouse gas emissions. Eight different NET‐producing transportation fuels and power‐generation technologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 75 publications
0
7
0
1
Order By: Relevance
“…However, the authors concluded that a large scale deployment of these CDR technologies does not remove sufficient CO 2 to achieve the climate goals of the Paris Agreement. Moreover, Li and Wright 31 presented a CDR technology review of the technoeconomic and life-cycle performance of biomass production pathways used for the production of transportation fuels and power generation technologies. Besides, Goglio et al 23 presented a review of the current challenges in LCAs related to Greenhouse Gas Removal Technologies (GGRTs), and gave useful recommendations for future LCAs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors concluded that a large scale deployment of these CDR technologies does not remove sufficient CO 2 to achieve the climate goals of the Paris Agreement. Moreover, Li and Wright 31 presented a CDR technology review of the technoeconomic and life-cycle performance of biomass production pathways used for the production of transportation fuels and power generation technologies. Besides, Goglio et al 23 presented a review of the current challenges in LCAs related to Greenhouse Gas Removal Technologies (GGRTs), and gave useful recommendations for future LCAs.…”
Section: Introductionmentioning
confidence: 99%
“…In all regions, the highest biofuel production volumes were observed for HDPO. Notwithstanding, HDPO has not achieved commercial stage and is less mature than other biofuel technologies (Figure 21) [88][89][90][91][92][93]. Thus, investing in technologies that are closer to the commercialization stage in the near-to mid-term, may accelerate the uptake of maritime biofuels, despite their lower yields.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the system boundary, allocation/system expansion, data availability and accuracy, parameter uncertainty, permanence of CO 2 removal, and the need for common guidelines in LCAs for NETs has been also highlighted (McQueen et al, 2021b). In this regard, the integration of LCA with techno-economic analysis (TEA) can decrease NETs uncertainty and improve technology readiness levels (TRL) (Li and Wright, 2020).…”
Section: Life Cycle Assessment On Geochemical Netsmentioning
confidence: 99%